L’apprentissage hybride en sciences de gestion : ce qu’en pensent les étudiants - Jean-Pierre Béchard; Catherine Carré; Gabriella Frankel; Zoffirath Dissou; Céline Bazinet; Gilles Cazabon; Yves Goyette (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Dealing with an increasingly competitive environment, business schools and faculties are more and more engaged in hybrid learning approaches. This is why our institution designed and implemented a blended-learning project during the years 2009 to 2011 in ten distinct courses for a total of 27 groups. We gathered the perceptions of 805 students in order to better understand their reasons for enrolling in such a course, their level of satisfaction with the teaching and learning environment and their views regarding the impacts on learning. All the results coming from a questionnaire were analyzed in view of evaluating pedagogical innovation and its potential for institutionalization. The article ends with four proposals grounded in a theoretical framework on hybrid learning and teaching.